Distributions of selected dissolved trace metal in Unimas Lake - Cinderella, Anak Embaki (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study on trace metals concentrations in water and sediment at selected stations of UNIMAS Lake were carried out. Water and sediment samples were collected from five stations where at different depth; surface, middle, bottom and five sediment samples were are collected for at same stations. Trace metals level in water and sediment were analyzed using Atomic Absorption Spectrometer (AAS). The result of water quality analysis shows that UNIMAS Lake is still in the range of good quality, clean and safe for recreational activities. Trace metals Fe, Ni, Cr, Cd were detected in water samples. However Cd, Pb, Cu and Zn were not detected due to below detection limit (BOL) of the AAS. In sediment samples, trace metals concentration followed the order: Fe> Zn > Cr > Cu > Pb > Cd, Ni. Cd and Ni concentrations below detection limit (BOL) and the concentration of Fe was higher in sediments due to anthropogenic activities. Enrichment Factor (EF) of trace metals in sediments were calculated and in a range of 0.09 - 3.53 and the Geo-accumulation Index (Igco) were calculated and indicate that were no pollution to moderately pollution in UNIMAS lake.